On Ideal Amenability of Banach Algebras - Jabbari, A. (Журнал математической физики, анализа, геометрии, 2012)
Let A be a Banach algebra. The Banach algebra A is said to be ideally amenable if every continuous derivation from A into I¤ is inner, where I is a two-sided ideal of A. In this paper, we consider the ideal amenability of Banach algebras, and try to give some new results on the ideal amenability of Banach algebras and commutative Banach algebras. Пусть A - банахова алгебра. Банахова алгебра A называется идеально аменабельной, если всякое непрерывное дифференцирование из A в I* , где I - двусторонний идеал A, внутреннее. Мы рассматриваем идеальную аменабельность банаховых алгебр и представляем новые результаты, полученные для идеальной аменабельности банаховых алгебр и коммутативных банаховых алгебр.